Criminal law sanctions for misappropriation, embezzlement or seizure of property through abuse of office - I. I. Cherkashyn; Yu. V. Filei (Law and Safety)
The concept of criminal law sanctions has been analysed, the classification of criminal law sanctions for misappropriation, embezzlement or seizure of property through abuse of office has been studied, and the peculiarities of building criminal law sanctions for crimes under Article 191 of the Criminal Code of Ukraine have been revealed. It has been concluded that a sanction is a mandatory component of an article (or part of an article) of the Special Part of the Criminal Code of Ukraine which contains a model of the type and scope of punishment which is adequate to the social danger of a criminal act. The sanction reveals the legal aspect of criminal punishment, indicating its type and scope, while acting as a model of criminal punishment provided for the crime.